ODA management in the South African health sector: a critical analysis - Molapo, Batho Rufus (My University, 2011)
The concept of aid effectiveness, which emerged in the 1990s when developed countries realised that the aid they were providing was not leading to intended results , can be described as the extent to which development aid is disbursed and employed in order to meet the development needs in a specific area. The concept is mostly espoused and advocated by the OECD through its 2005 Paris Declaration. There are major debates about the factors affecting the effectiveness of development aid. Similarly, a related question that could be asked is about the appropriateness of the Paris Declaration as the guiding framework for aid effectiveness, especially in middle income countries such as South Africa that are capable of formulating their own policies. Does the declaration, as it is, enhances or inhibits aid effectiveness? The aim of the research study is to find answers to these important questions. The health sector is utilised as a case study because it is the sector that receives more ODA than others. To undertake this analysis, two critical questions are posed, namely, to what extent are the principles of the Paris Declaration being applied in the South African public health care context?, and to what extent is the Paris Declaration relevant as a guiding framework for aid management in South Africa? The thesis looks at some ODA projects as well as South African policies and guidelines in relation to the Paris Declaration. After reviewing ODA overall in the health sector, a case study of GIZ is undertaken to present a more detailed analysis. The study finds that (i) the Paris Declaration is another form of the Good Governance agenda that is imposed on developing countries by developed countries, while they are not prepared to abide by the declaration (ii) although there is some level of alignment between the funding provided and the priorities of the sector, there is a huge donor focus on HIV/AIDS, which is nether entirely appropriate nor efficient, given that there many other problems and constraints and a dysfunctional healthcare system (iii) the fact that most of the HIV/AIDS prevention interventions are not locally created render them less effective (iv) the fact that most of the funding is not budget support but project support contributes to misalignment, while allowing donors to take ownership of projects (v) increased funding does not per se means better aid, and just pumping money into health sectors does not necessarily improve recipient’s health outcomes. (vi) there is insufficient harmonisation of donor activities in the health sector, and insufficient attention is paid to strengthening of health systems. Finally that the Paris Declaration is an adapted tool for improving aid efficiency in the context of a middle income country such as South Africa which has enough capacity to develop its own (owned) health policy, but is too shallow and does not take into account other intricacies related to development planning in a middle income country like South Africa. The study generally recommends a more centralised and stringent ODA management practice in South Africa. This, it is argued will contribute to a more coordinated approach. Moreover, as it is articulated in the recommendations, the implication of the findings is that other priorities, especially those that relate to system building should be taken into account as they have a bearing on the success of other initiatives such as HIV/AIDS treatment and prevention. Lastly, the study calls for local generated HIV/AIDS prevention approaches to be taken into account by donors in their interventions.
M.A. Faculty of Humanties, University of the Witwatersrand, 2011